School (socie)ties: individual and school level differences in the association between ethnic/racial victimization and academic functioning - da Cunha, Josafá M.; Santo, Jonathan B. (Frontiers in Education, 2023)
The current study aimed to expand on the existing literature by examining the effect of race-based victimization on academic functioning in a nation-wide sample of Brazilian youth. The ENEM 2009 dataset contained academic functioning scores of 795,924 Brazilian students from 25,488 schools. Above and beyond the effect of general victimization, ethnic/racial victimization was significantly negatively related to academic functioning with differences across ethnic/racial groups its in the effects. More interesting is that diversity climate at the school level buffered the association between ethnic/racial victimization and academic functioning. The effects were further qualified by school level ethnic/racial diversity and victimization. The current findings illustrate the pernicious effects of ethnic/racial victimization even after controlling for other forms of victimization. Moreover, differences in these associations across schools were accounted for using a combination of school level racial diversity and victimization with school level diversity climate emerging as a buffer of the effects of ethnic/racial victimization.